Citizens and E-government evaluating policy and management - Reddick, Christopher G.; Gale Group (Hershey, Pa. Information Science Reference, 2010)
Examines the role that citizens play in the development of electronic government or e-government, specifically focusing on the impact of e-government and citizens while exploring issues of policy and management.
section 1. Theoretical and conceptual issues. ch 1. Designing, implementing, and evaluating user-centered and citizen-centered e-government ; ch 2. A user-centric approach in e-government policies : the path to effectiveness? ; ch 3. Evaluating the impact of e-government on citizens : a cost-benefit analysis ; ch 4. Effectiveness of e-government in delivering services ; ch 5. An evaluation framework for e-government projects ; ch 6. Images of citizenship : a content analysis of local government websites in the United States ; ch 7. Innovation in democratic e-governance : benefitting from Web 2.0 applications in the public sector ; ch 8. Reducing the administrative burden by online information and referral services -- section 2. Issues and challenges. ch 9. Transparency and e-government in developing countries : the case of Latin-American municipalities ; ch 10. Human factors in implementing e-government in developing countries ; ch 11. E-government, security, and cyber-privacy : individual rights versus government responsibility ; ch 12. Considering the role of e-government in cybercrime awareness and prevention : toward a theoretical research program for the 21st century ; ch 13. Citizen centric or government centric? : perceptions of risk in new identity management systems ; ch 14. Citizens and service channels : channel choice and channel management implications ; ch 15. Comparing citizens' use of e-government to alternative service channels ; ch 16. Social tagging to search and recommend government information -- section 3. Case studies. ch 17. Engaging citizens on the internet : an assessment of local governments in Ohio ; ch 18. Assessing e-government services : the case of e-filing of personal income tax in Malaysia ; ch 19. Factors influencing intention to use e-government services among citizens in Malaysia ; ch 20. Assessing China's e-government and its impact on government and citizen relationship ; ch 21. Exploring citizens' visions of 2020 e-government in Taiwan : results from a 2008 scenario workshop ; ch 22. Evaluation of e-government services : a citizen-centric approach to citizen e-complaint services ; ch 23. Engaging citizens through local e-government : an Australian experience ; ch 24. Community policing in India : transparency through e-governance.
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Internet in public administration; Electronic government information; Electronic public records; Government Web sites; Political participation -- Technological innovations; Electronic books